Economic Contraction from COVID-19 in the Pacific: Implications for Health Financing. Issue 1 (1st December 2020) - Tandon, Ajay; Ivatts, Susan; Cowley, Peter; Roubal, Tomas; Dodd, Rebecca; Pepperall, Jane; Mikkelsen-Lopez, Inez; Irava, Wayne Jeremy; Palu, Toomas
ABSTRACT: Pacific Island countries (PIC) have emerged as among the most at-risk globally from the collateral economic damage resulting from the COVID-19 pandemic, despite being largely spared its direct health effects so far. Current projections indicate that all PIC will experience an economic contraction in 2020, ranging from −1.0% in Tuvalu to −21.7% in Fiji, worse than most countries globally on average. Given that more than 80% of financing for health in the Pacific comes from domestic and external public sources, the net impact of the economic contraction on resources for health will depend on whether overall public spending can offset the decline in economic activity and how health will be prioritized in government budgets relative to other sectors. Without active reprioritization, most countries could see a slowdown or even decline in per capita levels of public spending for health in the region, risking gains made in advancing universal health coverage in recent years. If health ministries do not act quickly and in consort with other ministries (particularly ministries of finance), including by taking active steps to improve the efficient use of existing resources and other measures to mitigate the economic effects of the crisis on resources for health, it is likely that current economic circumstances will result in unplanned changes. These changes may not deliver the health outcomes that the health ministries would select themselves and may result in a reversal of hard-fought health gains.